The role of morphology and function of intrinsic foot muscles in young handball players with chronic ankle instability - Llamas-Ramos, R.; San Antolín-Gil, M.; García-García, D.; Calvo-Lobo, C.; Alvarado-Omenat, J. J.; Ceballos-Laita, L.; Jiménez-Del-Barrio, S.; Rodríguez-Sanz, D.; Llamas-Ramos, I. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Strong evidence shows the importance of intrinsic foot muscles (IFMs) in balance and foot and ankle biomechanics; despite this, not much research has been published regarding the role of IFMs on chronic ankle instability. The aim of the study was to compare IFMs morphology and function between young handball players with and without chronic ankle instability. The secondary objective was to assess the association between the morphology or function of the IFMs and the foot morphology.